2003
DOI: 10.1101/gad.1097103
|View full text |Cite
|
Sign up to set email alerts
|

cAMP promotes pancreatic β-cell survival via CREB-mediated induction of IRS2

Abstract: The incretin hormone GLP1 promotes islet-cell survival via the second messenger cAMP. Here we show that mice deficient in the activity of CREB, caused by expression of a dominant-negative A-CREB transgene in pan-creatic-cells, develop diabetes secondary to-cell apoptosis. Remarkably, A-CREB severely disrupted expression of IRS2, an insulin signaling pathway component that is shown here to be a direct target for CREB action in vivo. As induction of IRS2 by cAMP enhanced activation of the survival kinase Akt in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
472
3
16

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(517 citation statements)
references
References 26 publications
26
472
3
16
Order By: Relevance
“…IGF-1 is a known regulator of PI3-K/PKB, whereas the mechanisms that link the G protein-coupled GLP-1 receptor to cell survival pathways are not well understood. It has been suggested that activation of CREB, a cAMP-dependent transcription factor, may provide a direct link between the GLP-1 receptor and the PI3-K/PKB pathway through the enhanced synthesis of the upstream effector, insulin receptor substrate-2 [43]. Furthermore, cytokines have been reported to inhibit CREB activation [44].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 is a known regulator of PI3-K/PKB, whereas the mechanisms that link the G protein-coupled GLP-1 receptor to cell survival pathways are not well understood. It has been suggested that activation of CREB, a cAMP-dependent transcription factor, may provide a direct link between the GLP-1 receptor and the PI3-K/PKB pathway through the enhanced synthesis of the upstream effector, insulin receptor substrate-2 [43]. Furthermore, cytokines have been reported to inhibit CREB activation [44].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the CRE (cyclic AMP-responsive element) and c-Ets sites, located at −48 and −16, respectively, have been demonstrated to be involved in induction of the transcriptional activity of human Ccnd1 [28,29]. In particular, promotion of beta cell survival by GLP1 via the second messenger cyclic AMP was significantly reduced in mice deficient in CREB activity, leading to diabetes [30]. Thus, the increased activities of the −73 and −34 constructs in our promoter assay can be explained by the presence of these sites, which are conserved in both human and rat promoters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Elevations in blood glucose provide the most potent stimulus. Upon its uptake into beta cells, glucose oxidation in the pancreatic beta cell induces closure of K ATP channels, membrane depolarisation, calcium entry via voltage-sensitive L-type calcium channels, and consequent phosphorylation and thus activation of the transcription factor CREB [5,15,29], which is essential for beta cell function [1][2][3][4][5]. Two mechanisms for linking membrane depolarisation-induced elevations of intracellular calcium to the activation of CREB have been proposed, mostly based on studies in neuronal systems.…”
Section: Discussionmentioning
confidence: 99%
“…Among the multiple factors required for normal beta cell function is the transcription factor cyclic AMP response element binding protein (CREB) [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation